Proteolytic ectodomain shedding of membrane proteins in mammals—hardware, concepts, and recent developments. (5th July 2018) - Lichtenthaler, Stefan F; Lemberg, Marius K; Fluhrer, Regina
Abstract: Proteolytic removal of membrane protein ectodomains (ectodomain shedding) is a post‐translational modification that controls levels and function of hundreds of membrane proteins. The contributing proteases, referred to as sheddases, act as important molecular switches in processes ranging from signaling to cell adhesion. When deregulated, ectodomain shedding is linked to pathologies such as inflammation and Alzheimer's disease. While proteases of the "a disintegrin and metalloprotease" (ADAM) and "beta‐site APP cleaving enzyme" (BACE) families are widely considered as sheddases, in recent years a much broader range of proteases, including intramembrane and soluble proteases, were shown to catalyze similar cleavage reactions. This review demonstrates that shedding is a fundamental process in cell biology and discusses the current understanding of sheddases and their substrates, molecular mechanisms and cellular localizations, as well as physiological functions of protein ectodomain shedding. Moreover, we provide an operational definition of shedding and highlight recent conceptual advances in the field. While new developments in proteomics facilitate substrate discovery, we expect that shedding is not a rare exception, but rather the rule for many membrane proteins, and that many more interesting shedding functions await discovery. Abstract : This review gives an operational definition of shedding as a fundamental cell biological and (patho)physiological process, and summarizes our current understanding of sheddases and their substrates, mechanisms and roles.